Gait Analysis in Primary Total Knee Arthroplasty with and without Patellar Resurfacing： A Randomized Control Study - 徐义明 白跃宏 周俊 黎庆钿 梁娟 (Shanghai jiao tong da xue xue bao, 2010)
It is still controversial whether or not to resurface patella during primary total knee axthroplasty （TKA）. One of the reasons may be insensitive measurement tools. We conducted a randomized controlled study to compare kinematic and kinetic parameters of resurfacing and nonresurfacing patella with the Vicon gait analysis system. The results show that patient post-operative gait of the two groups improved compared to pre-operative gait. Part of gait parameters, knee flexion at heel-strike, double limb support time and maximum adduction angle appeared to be statistically difference in 3 months, but 12 months later, the gait parameters of the two groups had no significant difference. Therefore, it seems that the final function of knee after TKA is not related whether or not to resurface patella.